Spatial Temporal Analysis of Mesoscale Convective System to Asia-Australia Monsoon in East Java - Prasetyo Firdianto; Bangun Muljo Sukojo; Achmad Zakir; Adi Mulsani (Institut Teknologi Sepuluh Nopember, 2025)
Indonesia maritime continent has the formation of clouds that can develop and evolution into MCSs (Mesoscale Convective System). Asian-Australian monsoon has an important influence in determining activities of MCSs. Research gap is analysis of relation between monsoon and MCSs in East Java where is greatly influenced by the monsoon. The data are weather satellite of Himawari, zonal wind and meridional wind ERA-Interim Model 850 mb. Determination of the MCSs follows the physical characteristics in the Maddox algorithm and the AUSMI index follows the Kajikawa algorithm. The method used is quantitative analysis of coefficient of correlation and determination, and qualitative in the form of descriptive analytic. It can be known that the Asian-Australian monsoon has weak influence on the MCSs in the East Java. AUSMI index has the same pattern and phase with frequency of MCSs on seasonal.